The Influence Of Interpersonal Written Communication On Human Resources Performance In Small And Medium-Sized Enterprises (Smes) (Journal of Namibian Studies : History Politics Culture, 2023)
The success of Small and Medium-sized Enterprises (SMEs) depends critically on effective communication. The effectiveness of Human Resources (HR) experts is closely related to the caliber of written interpersonal communication in this situation. Given the resource limitations that SMEs frequently experience, written communication—including emails, memoranda, reports, and electronic correspondence—becomes a vital tool for disseminating information, recommendations, and criticism.In SMEs, written interpersonal communication takes on a greater significance because it promotes collaboration, dispute resolution, and overall organizational effectiveness. Unlike larger organizations, SMEs frequently have flat hierarchies, which encourage open communication between employees, managers, and HR specialists. As a result, written communication's clarity, tone, and content directly affect HR performance. Additionally, effective written communication promotes a unified corporate culture by assuring that workers are in sync with their obligations, roles, and organizational goals. In order to improve HR performance and overall organizational effectiveness, the study intends to provide SMEs with strategic insights. These insights will help SMEs write more effectively. This study offers nuanced insights on the complex nature of interpersonal written communication by drawing on qualitative research including HR specialists, managers, and staff from various SMEs. The results highlight how important clear written communication is for improving HR effectiveness and worker performance in SMEs.